Redox-Neutral TEMPO Catalysis Toward Direct Radical (Hetero)Aryl C–H Di- and Trifluoromethoxylation - Lee, Johnny W. (Angew Chem Int Ed Engl, 2020)
Applications of TEMPO(•) catalysis for the development of redox-neutral transformations are rare. Herein, we report the first TEMPO(•)-catalyzed, redox-neutral C–H di- and trifluoromethoxylation of (hetero)arenes. The reaction exhibits a broad substrate scope, has high functional group tolerance, and can be employed for the late-stage functionalization of complex drug-like molecules. Kinetic measurements, isolation and resubjection of catalytic intermediates, UV-Vis studies, and DFT calculations support the proposed oxidative TEMPO(•)/TEMPO(+) redox catalytic cycle. Mechanistic studies also suggest that Li(2)CO(3) plays an important role in preventing catalyst deactivation. These findings will provide new insight into the design and development of novel reactions through redox-neutral TEMPO(•) catalysis.